Novel risk factors for cardiovascular disease in rheumatoid arthritis (2013)
Since cardiovascular disease (CVD) is the most common cause of mortality in patients with rheumatoid arthritis (RA), we aimed to determine factors associated with such a complication in a large series of Colombian patients. This was a cross-sectional analytical study in which 800 consecutive Colombian patients with RA were assessed for variables associated with CVD. Furthermore, a systematic literature review was performed to address the state of the art about non-traditional risk factors for CVD in RA. The preferred reporting items for systematic reviews and meta-analyses guidelines were followed in data extraction, analysis, and reporting of articles selected. Hypercholesterolemia, type 2 diabetes mellitus, abnormal body mass index, abdominal obesity, and current smoking were all traditional risk factors significantly associated with CVD in Colombians. As non-traditional risk factors, familial autoimmunity, more than 10 years of duration of the disease, patients working on household duties, use of systemic steroids, and low education level were associated with CVD in the studied population. Out of a total of 9,812 articles identified in PubMed and Scopus databases, 140 fulfilled the eligibility criteria and were included. Through this systematic review, several factors and outcomes related to CVD were confirmed and identified. These were categorized into genetics, RA-related, and others. Traditional risk factors do not completely explain the high rates of CVD in patients with RA; thus, novel risk factors related to autoimmunity are now recognized predicting the presence of CVD as strong as traditional risk factors. Our results may assist health professionals and policymakers in making decisions about CVD in patients with RA. © 2013 Springer Science+Business Media New York.